Examining the CEO’s impact on strategic changes in technology organizations - Yockelson, Alessandra Ginante (2020)
This research is in the field of Strategic Management, and it relates to how CEOs impact strategic change in the pursuit of competitive advantages for their firms. The research objective is to answer the following question: how do CEOs impact firms’ strategic changes in highvelocity technology markets? It draws from the emerging field of study of dynamic managerial capabilities, a term defined as “the capabilities with which managers build, integrate, and reconfigure organizational resources and competences” and coined by Adner and Helfat (2003, p.1012) in their attempt to explain the causes of firm idiosyncrasies that lead to performance variances among organizations. This multiple case study is exploratory and qualitative, and it contributes to understanding how the so-called CEO effect (Lieberson & O’Connor, 1972; Bertrand & Schoar, 2003; Crossland & Hambrick, 2011; Fitza, 2014; Quigley & Hambrick, 2015; Quigley & Graffin, 2017), a construct extensively studied across industries, may apply to individual firms, given that little is known about the process by which CEOs impact strategic change. Moreover, the study contributes to expanding the underpinnings put forward by dynamic managerial capabilities scholars as well as to the limited set of empirical studies available on dynamic managerial capabilities. The main findings are that CEOs impact strategic change by purposefully steering the multileveled interplay of individual capital possessed both by themselves and by the top management team; the relational capital nurtured in one-to-one relationships; the organizational capital, enacted predominantly by the management system; and the reputational capital that resides between the CEOs and all individuals who know of their existence. The CEO’s cognition, human capital, and social capital were identified as individual underpinnings for strategic change, and equally important, the CEO approachability and interpersonal skills in combination with the orientation towards customers, and the CEO’s high expectations pertaining to the caliber of the TMT. The most relevant underpinnings of relational capital were: the CEO's ability to provide direction, his or her encouragement to risktaking, the behavioral integration in the TMT, and the CEO efforts to mitigate silos. The sacred rituals of the firm’s management model, which in turn reinforces its culture model, and yields unity around the company’s vision, were the patterns related to organizational capital. Lastly, the CEOs’ visibility and storytelling around the strategic change, behavioral modeling for others, and signaling for self-selection make up their reputational capital.